Hubungan Daya Ledak Otot Tungkai Terhadap Hasil Lompat Jauh Di Sd Negeri 02 Pasmah Air Keruh - Noprison, Noprison; Juwita, Juwita; Martiani, Martiani (Educative Sportive, 2024)
This research aims to: (1) determine the leg muscle explosive power of male fifth-grade students at SD Negeri 02 Pasmah Air Keruh Kepahiang. (2) The results of the long jump performance of male fifth-grade students at SD Negeri 02 Pasmah Air Keruh Kepahiang. (3) To investigate the relationship between leg muscle explosive power and long jump performance at SD 02 Pasmah Air Keruh. This study is a correlational descriptive research conducted at SD 02 Pasmah Air Keruh, Kepahiang Regency, Bengkulu Province. Research Procedure The research activities include several stages: (1) Standing broad jump test. (2) Preparing the equipment. (3) Test implementation. (4) Recording the results. Data collection technique in this research uses measurement test technique, while the data analysis technique includes test results, prerequisite test, and correlation test. The research results indicate that the leg muscle explosive power test results for fifth-grade students at SD Negeri 02 Pasmah Air Keruh fall into the "Sufficient" category. Based on the long jump test results, the average score is 4.29, which falls into the "Good" category. Based on the correlation test results, the significant value of leg muscle explosive power on long jump performance is 0.000, indicating a significant relationship between leg muscle explosive power and long jump performance with a Pearson Correlation coefficient of 0.819, signifying a high degree of correlation.